Efficacy and safety of anti-vascular endothelial growth factor agents in the treatment of primary pterygium - Zhang, Bowen; Dong, Xingmei; Sun, Yi (Frontiers in Medicine, 2023)
Purpose: To further evaluate the efficacy and safety of anti-vascular endothelial growth factor (VEGF) agents in management of primary pterygium. Methods: Randomized controlled trials (RCTs) in databases of PubMed, Web of Science, Embase, and the Cochrane Central Register of Controlled Trials were searched from inception to September 2022. Recurrences and complications were evaluated as the pooled risk ratio (RR) and 95% confidence interval (CI) using random-effects model. Results: 1096 eyes in 19 RCTs were included. Anti-VEGF agents statistically decreased recurrence rate of pterygium following surgery (RR 0.47, 95% CI 0.31–0.74, P<0.001). Subgroup analysis showed that anti-VEGF as an adjunct to bare sclera (RR 0.34, 95% CI 0.13–0.90, P=0.03) and conjunctival autograft (RR 0.50, 95% CI 0.26–0.96, P=0.04) statistically reduced recurrence rate, while the effect was not favorable for conjunctivo-limbo autograft (RR 0.99, 95% CI 0.36–2.68, P=0.98). Anti-VEGF agents statistically decreased recurrence in White patients (RR 0.48, 95% CI 0.28–0.83, P=0.008), while didn’t in Yellow patients (RR 0.43, 95% CI 0.12–1.47, P=0.18). Both topical (RR 0.19, 95% CI 0.08–0.45, P<0.001) and subconjunctival anti-VEGF agents (RR 0.64, 95% CI 0.45–0.91, P=0.01) had a positive influence on recurrence. There was no statistically significant difference in complications between the groups (RR 0.80, 95% CI 0.52–1.22, P=0.29). Conclusions: As adjuvant treatment, anti-VEGF agents statistically reduced the recurrence following pterygium surgery, especially among White patients. Anti-VEGF agents were well tolerated without increased complications.